Improved performance of impact ionization MOSFETs by using dopingless concept and strained channel. (September 2017) - Kumar, Mirgender; Park, Si-Hyun
Abstract: This simulation based study provides an improved performance for impact ionization SOI FETs by using strained channel and dopingless concept. Dopingless concept based on work function engineering have also introduced a new conduction mechanism for impact ionization devices with electron current at bottom interface and hole current at top interface, which is reverse phenomenon in compare to conventional device. Bipolar current also modeled with its different component in the channel. Significant increment in impact generation rate with increasing strain is observed, which leads to decrement in supply voltage below 1 V and makes this device competitive with impact ionization based junctionless devices for additional advantage of high carrier mobility. The effect of different device parameters is examined to optimized and improved performance. The device shows the quasi-ideal subthreshold switching characteristics (<1 mV/dec) with Ion /Ioff ratio of 10 6 . Highlights: Dopingless strained-si MOSFETs have examined with the faster switching speed. Significant increment in impact generation rate with increasing strain is observed. It makes this device competitive with impact ionization based junctionless devices for high carrier mobility.